The role of CHMP2B in frontotemporal dementia. (20th January 2009) - Urwin, Hazel; Ghazi-Noori, Shabnam; Collinge, John; Isaacs, Adrian
Abstract : Mutations in the CHMP2B (charged multivesicular body protein 2B) gene that lead to C-terminal truncations of the protein can cause frontotemporal dementia. CHMP2B is a member of ESCRT-III (endosomal sorting complex required for transport III), which is required for formation of the multivesicular body, a late endosomal structure that fuses with the lysosome to degrade endocytosed proteins. Overexpression of mutant C-terminally truncated CHMP2B proteins produces an enlarged endosomal phenotype in PC12 and human neuroblastoma cells, which is likely to be due to a dominant-negative effect on endosomal function. Disruption of normal endosomal trafficking is likely to affect the transport of neuronal growth factors and autophagic clearance of proteins, both of which could contribute to neurodegeneration in frontotemporal dementia.